Percepce postojů občanské veřejnosti a komunikace s municipalitou - Brychtová, Šárka; Duplinský, Josef (Univerzita Pardubice, 2003)
Knowledge of citizens' attitudes, needs and interests appears to be a primary starting point for research analyses of the public opinion and communication in public administration. Correct conclusions from such research can become a starting point point for successful communication of an institution with the community. The article aims to provide an empirical study of the public opinion relating to work of the public administration, and typical negative phenomena in communication of their representatives with the general public.
Keywords: občanská společnost; veřejnost; municipalita; Komunikace